Crossbreeding for increased beef production. 1. Performance of crosses between local breeds and either Santa Gertrudis or Red Poll - Ngere, L.O.; Cameron, C.W. (1972)
The effects of crossbreeding on production performance are investigated. The performances of local pure lines from West African Shorthorn (WAS) and N'Dama cattle, and their crosses with Santa Gertrudis and Red Poll were evaluated over a period of 4 years. The F1 generation of Santa Gertrudis x WAS and Red Poll x WAS showed superior performance with respect to birth weight, post weaning growth rate, time to achieve 650-lb slaughter weight, response to supplementation in the dry season, size and overall conformation and age at-first-calving, as compared to N'Dama and WAS pure lines or their crosses. Comparable values were attained for both crossbreds and local pure lines for preweaning growth rates, weaning weights and calf hood mortality. The crossbreds experienced bigger weight losses during bad grazing conditions.